Design of 20MW Power in Co-Generation Plant by Using Bagasse and Partial Amount of Coal as Fuel - J. Suresh, C. Dinakaran, G. Ratnaiah, V. Vaishnavi (International Journal of Advanced Science and Technology, 2020)
This paper deals with generation of power in a Co-Generation plant by using bagasse and partial amount of Coal as fuel. There are several methods for generating the power. One of the important methods of generating the power is by constructing dam across the river. But this method is not economical and takes long time for construction. In this power plant the availability of water must be high which an important aspect in it is. The other method for generating power is through Nuclear power plant, Diesel power plant, Natural gas power plant etc. But these methods of power generation requires large amount of initial cost and maintenance cost. These power plants are very dangerous because they may explode under fault conditions which cause risk to life of the workers and villages surrounded by the power plant. In this proposed paper the power generated used for the sugar factory and transmitted to the APTRANSCO (i.e. 132KV Substation) through transmission lines and substations. By using the factories for both the generation of power and manufacturing of products there will be an increase in the power generation and decrease the power demand. The advantages of these plant is that it requires less amount of water and cost of fuel i.e., bagasse which is byproduct of sugar cane is free and coal is also cheap. The main advantage of these plant is power generation is high and requires less space for construction compared to hydro power plant. Most of the power supplied to the factories is used at the initial stage of running the plant and later the supply to the plant is produced by its own using the Co-Generation plant.